ANATOMICAL COMPARISON OF RAKTADHARA KALA WITH THE HELP OF ANIMAL MODEL, A PILOT STUDY. - Hiremath Mallikarjun S.; Kamble Pushpalata B. (International Journal of Applied Ayurved Research, 2016)
Saptakala are explained in Sustuta samhita sharir sthana ,adhyaya 4 and 5 with regards formation and nomenclature of Kala respectively. In Kalpasthan, Visa cikitsa, Acharya Sushruta has described about visaveg passing from one Kala to the other Kala and its importance. Raktadhara Kala is second in order and as the name indicates it is in relation with Raktadhatu. In present pilot animal experiment, aqueous extract of an organic irritant i.e. Gunja (Abrus precatorius) is administered with dose of 120 mg/kg body weight in albino mice. Both controlled and experimental animals were sacrificed on 7th day and visceral organs were sent for histo-pathological examination. Compared to other organs, liver and spleen have shown marked hemorrhagic and necrosis changes.The drug vitiates Raktadhatu due to its usna, tiksna guna. This Raktadhatu in turn vitiates Raktadhara Kala.